Siam-weeb based gelatin electrospun scaffolds - Mohamed, Nor Shamsiah; Jun Ham, Jun Ham; Ab-Rahim, Sharaniza; Cheng, Yee Low; Ching, Theng Koh (Microscopy Society of Malaysia (MSM), 2022)
Siam weed (Chromolaena odorata) is a traditional herb used to soothe burns and scars and potentially improve dressing and tissue-engineered construct healing ability. The use of Siam weed is mainly in the form of extract. The state of liquid extract limits the use of Siam weed compared to the state of gels and membrane. However, the development of the hybrid of Siam weed in gel and membrane form is lacking. In this study, Siam weed was harvested and made into aqua extracts. The biocompatibility of the aqua extract with various concentrations was tested using Cell Proliferation Assay. The aqua extract was then incorporated into the gelatin solution and spun into nanofibers using an electrospinning technique. The cell proliferation study shows maximum cell proliferation at the 25 μg/ml concentration. The scanning electron microscope images of the electrospun scaffolds show fibrous networks’ microstructures without beads. The concentration of the hybrid solution was found to affect the morphology of the nanofibers by having diameters in the range of 160 ± 90 to 250 ± 150 nm. The Siam-weed-based gelatin electrospun scaffolds provide a native-like microenvironment and potentially improve wound healing ability for biomedical application.